Investigation of sulfonation degree and temperature on structure, thermal and membrane's properties of sulfonated poly (ether ether ketone). (30th April 2023) - Zhang, Yuqing; Zhang, Ailing; Wang, Song; Li, Sanxi
Abstract: In this paper, the primary and secondary relationship among factors affecting the sulfonation of poly (ether ether ketone) (PEEK) was investigated in detail by a response surface method in order to solve the problem of performance deterioration caused by excessively high or low sulfonation. Acid-base titration, infrared analysis (FT-IR), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) proved that temperature had the greatest influence on PEEK sulfonation and the sulfonate group was successfully connected to the main chain and the proton conduction mechanism was in accordance with Arrhenius law. Under optimized conditions, 44% sulfonation degree of PEEK was selected to test the dimensional stability, microstructure and proton conductivity, and to explore the influence of temperature on the membrane's structure and performance. The result indicates that the microstructure has become more homogeneous at 60 °C, resulting in continuous proton conduction channels, demonstrating excellent proton conductivity (5.04 × 10 −2  S/cm). Highlights: Impact of the primary and secondary relationship among factors affecting sulfonation of PEEK was studied. Optimized sulfonation condition of SPEEK was suggested. The proton conduction mechanism obeys Arrhenius law. Explored the influence of temperature on the SPEEK44 membrane's structure and performance. Homogeneous structure represent continuous channels for proton conduction.